Interface between quantum-mechanical-based approaches, experiments, and CALPHAD methodology - Turchi, Patrice E.A.; Abrikosov, Igor A.; Burton, Benjamin; Fries, Suzana G.; Grimvall, Göran; Kaufman, Larry; Korzhavyi, Pavel; Rao Manga, V.; Ohno, Munekazu; Pisch, Alexander; Scott, Andrew; Zhang, Wenqing (Calphad, 2007)
The increased application of quantum-mechanical-based methodologies to the study of alloy stability has required a re-assessment of the field. The focus is mainly on inorganic materials in the solid state. In a first part, after a brief overview of the so-called ab initio methods with their approximations, constraints, and limitations, recommendations are made for a good usage of first-principles codes with a set of qualifiers. Examples are given to illustrate the power and the limitations of ab initio codes. However, despite the “success” of these methodologies, thermodynamics of complex multi-component alloys, as used in engineering applications, requires a more versatile approach presently afforded within CALPHAD. Hence, in a second part, the links that presently exist between ab initio methodologies, experiments, and the CALPHAD approach are examined with illustrations. Finally, the issues of dynamical instability and of the role of lattice vibrations that still constitute the subject of ample discussions within the CALPHAD community are revisited in the light of our current knowledge with a set of recommendations.